MESINIAGA TOWER - Suci Farahdilla (Rumoh, 2020)
Mesiniaga Tower is one of first generation buildings design for low energy consumption purpose. The building itself was completed in 1992 and was designed by Ken Yeang, an architect whose concern is to create a better performance of a building without having to increase its cost of operation. It is located in Malaysia, South East Asia, where the tropical climate has heat and humidity almost the same throughout the year. The concept of the building is bioclimatic design with the original concept of fully natural ventilation, but later the conventional cooling system was added. The architect’s idea is a tube shaped building with multiple terraces and openable windows to provide more wind and humidity in order to have a comfortable thermal condition. However these ideas lead to the problem of increasing yearly energy consumption. This paper then suggest the possible design strategies to improve the thermal comfort of Mesiniaga Tower as well as lower its annual cost such as radiative cooling, night cooling, ground cooling and passive downdraught evaporated cooling. The radiative cooling then gives the building of 8% cooling potential.